Preparation and Characterization of Carbon Quantum Dots by Sandal Wood - R.C Chhipa, Neetu Sharma Gaur (International Journal of Advanced Science and Technology, 2019)
The exploit of nanomaterial with extraordinary properties in scientific and technological applications has been an ongoing and very exciting research areas in the recent time .Nanomaterial offer unique properties such as high surface to volume ratio, high biochemical reactivity, ability to penetrate cells and swift distribution inside organism etc. Quantum dots are generally semiconductors Nano-crystals of physical dimension smaller then the Bohr radius .Carbon quantum dots (CQD) are a type of carbon nanoparticles with size less then 10 nm. Carbon quantum dots are prepared by sandal wood by hydrothermal method ,using Sulphuric acid , nitric acid and sodium hydroxide .By centrifugation it convert into precipitate form and finally dried in hot air oven and obtained powder form. These CQDs are used in drinking water treatment. In recent years ,an explosion of studies has been carried out to further improve the performance of CQDs for different applications, for eg. – Chemical sensor , bio-imaging, catalysis , photovoltaic drug and gene delivery. As prepared CQD is observed under UV spectroscopy.